2018
DOI: 10.1186/s12911-018-0651-5
|View full text |Cite
|
Sign up to set email alerts
|

SNOMED CT standard ontology based on the ontology for general medical science

Abstract: BackgroundSystematized Nomenclature of Medicine—Clinical Terms (SNOMED CT, hereafter abbreviated SCT) is a comprehensive medical terminology used for standardizing the storage, retrieval, and exchange of electronic health data. Some efforts have been made to capture the contents of SCT as Web Ontology Language (OWL), but these efforts have been hampered by the size and complexity of SCT.MethodOur proposal here is to develop an upper-level ontology and to use it as the basis for defining the terms in SCT in a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…Our previous studies demonstrated the benefits of using an ontology to build CDSSs [9, 10, 65, 66]. The formal and explicit semantics facilitate knowledge representation, sharing, and reuse.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated the benefits of using an ontology to build CDSSs [9, 10, 65, 66]. The formal and explicit semantics facilitate knowledge representation, sharing, and reuse.…”
Section: Discussionmentioning
confidence: 99%
“…According to Linked Data principles and best practices [ 42 ], the proposed Smart Health (SH) KG (available at ) reuses and combines well-known KGs. Basically, the Systematized Nomenclature of Medicine—Clinical Terms (SNOMED-CT) [ 56 ] has been adopted as upper ontology to model the taxonomy of both human anatomy and medical specialties. Moreover, specific clinical terms have been borrowed from the Uber Anatomy Ontology (UBERON) [ 57 ] and the Foundational Model of Anatomy (FMA) [ 58 ], extending the basic anatomical taxonomy with additional entities about human systems.…”
Section: Proposed Approachmentioning
confidence: 99%
“…This objective would provide great advantages for the outcome of each component in an EHR ecosystem. Hence, there is a great need for standards, ontologies, and medical terminologies [201]. 4.…”
Section: Mh Adds Another Level Of Complexity By Addingmentioning
confidence: 99%
“…Semantically intelligent CDSSs can use ontologies to infer hidden information with semantic relations by using description logic axioms, such as drug-drug interactions and comorbidity [36], [201], [202]. 4.…”
Section: B Mh and Cdss Challenges And Future Directionsmentioning
confidence: 99%